Implementation Of Permendag No. 31 Of 2023 On The Merger Of Tiktok Shop Social Commerce With Tokopedia E-Commerce And The Impact On Umkm Actors. Tokopedia E-Commerce And The Impact On Umkm Actors - Reynaldi Alfarisi Trideta; Adien Trisha Maulani; Tri Wulandari; Harmono Harmono; Deni Yusup Permana (PT Publikasiku Academic Solution, 2024)
This research focuses on exploring the extent to which the application/implementation of Permendag No. 31 of 2023 concerning Business Licensing, Advertising, Development, and Supervision of Business Actors in Trading Through Electronic Systems towards the Merger of Social Commerce TikTok Shop with E-commerce Tokopedia and how it impacts MSME actors which includes protection and an increase in their business turnover. This study aims to determine how the Implementation of Permendag No. 31 of 2023 is towards the merger of TikTok Shop with Tokopedia and to find out the impact on MSME players both in terms of Legal Protection and turnover income. In answering the problems in this study, we use a legal research method, namely Normative Juridical, where we focus on legal studies of Permendag No. 31 of 2023. The author examines the extent to which the implementation of the presence of the Permendag for MSME actors and the merger of TikTok Shop with Tokopedia. So in the end, we find the conclusion that the presence of this Permendag has fulfilled the need to protect business actors who carry out their activities through PMSE and the merger between TikTok Shop and Tokopedia which then merged into Shop Tokopedia which is currently managed under Tokopedia is by the contents of Permendag Number 31 of 2023, namely social commerce is not allowed to provide transaction services in it. Social media only functions as a social media service.